Pioneering the future of industrial Development:Harnessing Membrane separation Breakthroughs to propel CO2 extractiom from Natural gas into a Sustainable Era - Nnadikwe Johnson; Momoh Abdulazeez Adeyemi; Onuabuchi Azunna (Jurnal Teknik Indonesia, 2025)
Natural Gas (NG) processing is a prominent industrial separation process. Among the available techniques, the innovative membrane process shows potential for efficient removal of impurities, including carbon dioxide (CO2). This study focuses on utilizing breakthroughs in membrane separation to drive sustainable CO2 extraction from natural gas. Through comprehensive research and analysis, we explore the effectiveness and feasibility of membrane-based systems in removing CO2 impurities from NG, thus promoting greener and more sustainable industrial practices. Our findings underscore the transformative nature of membrane separation technology, presenting new possibilities for a more environmentally-friendly and sustainable approach to CO2 extraction from natural gas. Natural Gas (NG) processing utilizes various techniques for impurity removal, with the membrane process emerging as a promising option for efficient carbon dioxide (CO2) extraction. This research proposes the integration of a simple mathematical model into ASPEN HYSYS to design a membrane system for CO2/CH4 separation. The study also investigates parameter sensitivities by altering operating conditions, such as feed composition and pressure, as well as membrane properties, including selectivity. By analyzing these variables, we aim to optimize the performance and efficiency of the membrane system, facilitating the sustainable extraction of CO2 from NG. The findings contribute to advancing the design and operation of membrane-based processes for CO2 separation, paving the way for greener and more sustainable industrial practices.  In addition, this study explores various configurations for optimizing the design of the membrane system, including single stage with and without recycle, as well as double stage configurations. The investigation demonstrates that methane recovery can be enhanced through the recycling of the permeate stream and by implementing a double stage membrane system. These findings highlight the potential for improving the efficiency and performance of the membrane system, enabling higher methane recovery rates. By considering different configurations, this research contributes to the development of more effective and sustainable CO2 extraction processes from natural gas.